2018
DOI: 10.1002/oca.2397
|View full text |Cite
|
Sign up to set email alerts
|

Optimal control of nonlinear dynamical systems based on a new parallel eigenvalue decomposition approach

Abstract: Summary This manuscript aims to investigate a new approach based on the modal series method and eigenvalue decomposition technique to solve a class of nonlinear optimal control problems. For this purpose, a sequence of decoupled linear two‐point boundary value problems is solved iteratively instead of solving the coupled nonlinear two‐point boundary value problem derived from the maximum principle. The convergence analysis of the suggested technique is also investigated. In addition, the problem that needs to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 40 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…This theory for linear systems has been highly improved [26] , however, the nonlinear optimal control problem (OCP) has become a strong topic and should be deeper investigated [27][28] . Jajarmi and Baleanu [29] proposed a new approach based on the modal series method and eigenvalue decomposition technique to solve a class of nonlinear optimal control problems. They have also investigated the convergence analysis of their suggested technique.…”
Section: Introductionmentioning
confidence: 99%
“…This theory for linear systems has been highly improved [26] , however, the nonlinear optimal control problem (OCP) has become a strong topic and should be deeper investigated [27][28] . Jajarmi and Baleanu [29] proposed a new approach based on the modal series method and eigenvalue decomposition technique to solve a class of nonlinear optimal control problems. They have also investigated the convergence analysis of their suggested technique.…”
Section: Introductionmentioning
confidence: 99%
“…In the end of nineteenth century basic theory of fractional calculus was developed with the studies of Liouville, Grünwald, Letnikov, and Riemann. It has been shown that fractional derivative operators are useful in describing dynamical processes with memory or hereditary properties such as creep or relaxation processes in viscoelastoplastic materials [3] , [4] , impact problem [5] , plasma physics [1] , diffusion process models [6] , [7] , [8] , [9] , chaotic systems [10] , control problems [11] , [12] , dynamics modeling of coronavirus (2019-nCov) [13] , etc .…”
Section: Introductionmentioning
confidence: 99%
“…[21], gives a good view of nonlinear systems' dynamical behaviours [22][23]. This method was firstly developed for the analysis of dynamical systems with nonlinear terms [24][25][26], and recently it was extended for the optimal control and MPC of nonlinear dynamical systems [27][28][29]. Motivated by the remarkable advantages of the model series method, we aim to extend this technique in this paper to solve a class of discrete nonlinear OCPs.…”
Section: Introductionmentioning
confidence: 99%